Intercultural Approach in Foreign Language Teaching and Formation of Cultural Mediators: A Corpus Analysis of the Adjective polite in French and Polish - Dryjańska, Agnieszka (Taikomoji kalbotyra, 2021)
This study aims to analyse the notion of politeness through the collocations of the adjective polite and its Polish equivalents, i.e. grzeczny and uprzejmy, chosen as cultural keywords in order to verify and expand the conclusions of my previous research on the noun politeness. The study has a double perspective. It is based on a linguistic corpus-based analysis of French politeness in a contrastive approach to French and Polish data. Also, the study considers ways of integrating such data into foreign language teaching. The research is carried out on three corpora: the French language corpus Frantext, the National Polish Language Corpus (NKJP) and the Leipzig Corpora Collection. The study includes the analysis of frequency classes of the three words and their most frequent collocations identified on the basis of different measures of association between co-occurring words. By integrating the results of this linguistic approach into language teaching, it is possible to clarify certain semantic subtleties of the words polite, grzeczny and uprzejmy and explain to the learners why these words are not perfect equivalents, or how linguistic analysis reveals cultural differences. Complex approach promoted in this paper may contribute to the development of the intercultural awareness in foreign language teaching and cultural mediation.
Keywords: polite; politeness; intercultural approach; cultural mediator; corpus analysis; semantic analysis; collocations